"2x-1-1=x-3-&" のYouTube検索結果 - ユーティージェーピー





 

このキーワードで検索する人は他にこんなワードでも調べています!


2x-1-1=x-3-(-5+x)     2x-3(x-1)=4+2(x-1)     x^2-2x/x-1-2x-1/1-x=3     solve 2(2x-1/x+3)-3(x+3/2x-1)=5     2(2x-1/x+3)-3(x+3/2x-1)=5     2(x+1)(x-1)-(2x+3)(x-2)=0     3(2x-1) 4+5(x-1)     3(2x-1)+5=6(x+1)     y=(1/x+1)(2x-3)     f^2(1+2x)=x^3(x-1)    
 

2x-1-1=x-3-&のYouTube動画検索結果 : ページ中  ページ目


一度に検索結果を閲覧できるのは500件までとなっています。見たい情報が見つからない場合は、キーワードを変更するかお好みの条件で絞り込んでください。

動画の並べ替え 投稿日で絞り込み この条件で絞り込み

検索結果 : 500件
最初のページ
最初のページ
前のページ
前のページ
次のページ 次のページ 最後のページ 最後のページ

2x-1-1=x-3-&のYouTube動画検索結果  件目から件目



x+1/x=5 then find the value of x^2+1/x^2 and x^3+1/x^3 | Mathematics Questions and Answers

Mathematics , Numerical Ability , Arithmetic Ability, Important Formulas x+1/x=5 then what is the value of x^2+1/x^2 and x^3+1/x^3 ?
投稿日時:2016年09月13日 21時42分


コメント数:件

ECUACIONES E INECUACIONES

ECUACIONES DE PRIMER GRADO ¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯ [00:05] (01) x + 4 = 1 [00:58] (02) x - 3 = 6 [01:53] (03) 7 + x = 9 [02:18] (04) 11 - x ...
投稿日時:2015年04月15日 01時49分


コメント数:件

Solving Exponential Equations: Exact Answer for 7^x+3=4^2x-1

When x is in the exponent and you can't get a common base, you have to LOG both sides of the equation and rearrange to solve for x.
投稿日時:2014年08月26日 05時24分


コメント数:件

6x+5(2-3x)=3(2x -1)

Solve the linear equation 6 - 3(4-3x)=2(x+1). See http://www.helpudomaths.co.uk for more videos on linear equations Please leave a comment if this has helped.
投稿日時:2014年04月26日 09時49分


コメント数:件

*Graph Rational Functions: y = (2x+1)/(x-3)

A http://www.door2math.com production. Dr. Pan makes learning math Fun. What is the domain and range of y = (2x+1)/(x-3)?
投稿日時:2011年06月9日 08時54分


コメント数:件

*Graph Rational Function: f(x)=(4x+3)/(2x-1)

A http://www.door2math.com production. Dr. Pan makes learning math Fun.Given the function f(x)=4x+3/2x-1 What are the coordinates of the point of intersection ...
投稿日時:2011年06月9日 09時22分


コメント数:件

2x+1/3 - x-3/4 = x/2

Resolução da equação 2x+1/3 - x-3/4 = x/2.
投稿日時:2016年07月21日 00時28分


コメント数:件

Lim (x^2+2x-1) x tiende a 2 [Cálculo 1]

Lím (x^2+2x-1) x-- 2 Resolveré este problema, separando los límites o puedes remplazar directamente, utilizando los teoremas. TEOREMAS 1) lim (mx + b) ...
投稿日時:2016年08月20日 04時06分


コメント数:件

(3x-5)/3 = (2x+1)/4

Solve the equation (3x-5)/3 = (2x+1)/4. This assumes basic knowledge. See http://www.helpudomaths.co.uk for more such videos. Please comment if you found ...
投稿日時:2014年04月27日 06時09分


コメント数:件

Límite (2x + 1/x^2 - 3x + 4) x tiende a -1 [Cálculo 1]

Lím (2x+1/x^2 - 3x + 4) x-- -1 Resolveré este problema, separando los límites o puedes remplazar directamente, utilizando los teoremas. TEOREMAS 1) lim (mx ...
投稿日時:2016年09月22日 04時08分


コメント数:件

Solve tan(x/2)=-sqrt(3) and sin(2x)=-1/2

(a) tan(x/2)=-sqrt(3) (b) sin(2x)=-1/2.
投稿日時:2014年04月21日 12時36分


コメント数:件

Límite (2x-1)^3 x tiende a 0 [Cálculo 1]

Lím (2x-1)^3 x-- 0 ALGEBRA (a+b)^3= (a)^3 + 3(a)^2(b) + 3(a)(b)^2 + (b)^3 (a-b)^3= (a)^3 - 3(a)^2(b) + 3(a)(b)^2 - (b)^3 TEOREMAS 1) lim (mx + b) = ma + b ...
投稿日時:2016年10月11日 12時19分


コメント数:件

Integrate (x^2 - 2x - 1)/((x-1)^2(x^2+1)) dx

Integrate (x^2 - 2x - 1)/((x-1)^2(x^2+1)) dx.
投稿日時:2017年01月31日 01時58分


コメント数:件

2(x+1)/3 - 3(x+2)/4 = (x+1)/6

Resolução da equação 2(x+1)/3 - 3(x+2)/4 = (x+1)/6 MMC, distributiva.
投稿日時:2016年07月21日 02時16分


コメント数:件

integrate (x^2 + 2x - 1)/(x^3 - x) dx

integrate (x^2 + 2x - 1)/(x^3 - x) dx.
投稿日時:2017年01月31日 01時47分


コメント数:件

Integrate e^2x -1/e^2 x +1

 
投稿日時:2017年03月20日 23時33分


コメント数:件

Limite (2x+1) x tiende a 4 [Cálculo 1]

Lím (2x+1) x-4 Resolveré estos problemas en 2 formas, separando los límites y remplazando directamente, utilizando los teoremas. TEOREMAS 1) lim (mx + b) ...
投稿日時:2016年08月1日 14時10分


コメント数:件

Solve for x :: 1/(2a + b + 2x) = 1/2a + 1/b + 1/2x || Quadratic Equation HOTS 10 ||

Popular And Recommended Videos: 1)How to use Log Tables Basic Knowledge part 1 of 1 : http://bit.ly/2uAHvFK 2)How to use Log Tables in Solving Question ...
投稿日時:2017年10月27日 23時30分


コメント数:件

Factor x^(-3/2) + 2x^(-1/2) + x^(1/2)

Factor x^(-3/2) + 2x^(-1/2) + x^(1/2) completely.
投稿日時:2013年11月5日 07時09分


コメント数:件

Divide by long division: (7x^3-3x^2-2x-1) divided by (x-1)

Watch as I use long division on (7x^3-3x^2-2x-1) divided by (x-1). I did forget to write the answer until the end, I was having so much fun! Would you like your ...
投稿日時:2015年04月12日 08時58分


コメント数:件



スポンサードリンク

↑ PAGE TOP